Driving the Cashless Economy: The Influence of QRIS Utilization on Consumer Purchase Intention in Surakarta - Sari, Novi Puspita; Putri, Eskasari (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the influence of payment technology, non-cash payment, purchase intention, and community interest on the use of the Quick Response Code Indonesia Standard (QRIS) among the people of Surakarta. The research employs a quantitative approach with primary data collected through an online questionnaire during the 2021–2023 period. The sample was obtained using cluster random sampling, involving Surakarta residents who had used QRIS at least once and exhibited a high level of purchase intention. The dependent variable is QRIS usage, while the independent variables include payment technology, non-cash payment, purchase intention, and community interest. Data analysis was conducted using multiple linear regression after validity, reliability, and classical assumption tests. The findings indicate that payment technology, non-cash payment, purchase intention, and community interest significantly affect QRIS usage. This study provides empirical insights into the factors driving QRIS adoption in Surakarta and serves as a foundation for future research in other regions.